Promoting International Energy Security Volume 4, The Gulf of Guinea - Johnson, Stuart E. (RAND Corporation, 2012)
Nigeria is an important oil producer, but security shortfalls impede oil production and new investment. Important new finds of oil and natural gas have been reported in the territorial waters of Nigeria and nearby nations. Making the offshore petroleum infrastructure more secure would promote additional oil field investment, leading to greater production. The U.S. Air Force has expertise that could help build local security capabilities.